2018
DOI: 10.1186/s12890-018-0662-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of peak inspiratory flow rate via the Breezhaler®, Ellipta® and HandiHaler® dry powder inhalers in patients with moderate to very severe COPD: a randomized cross-over trial

Abstract: BackgroundThe chronic and progressive nature of chronic obstructive pulmonary disease (COPD) requires self-administration of inhaled medication. Dry powder inhalers (DPIs) are increasingly being used for inhalation therapy in COPD. Important considerations when selecting DPIs include inhalation effort required and flow rates achieved by patients. Here, we present the comparison of the peak inspiratory flow rate (PIF) values achieved by COPD patients, with moderate to very severe airflow limitation, through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 22 publications
1
52
0
3
Order By: Relevance
“…VOLUME (L) is the mean in an upright standing position, and verbal encouragement was given to help the subjects perform maximally. For each patient, the highest value of the inhalation, out of 3 repeat inhalations, was selected for analysis (24,25).…”
Section: Measurement Protocolmentioning
confidence: 99%
“…VOLUME (L) is the mean in an upright standing position, and verbal encouragement was given to help the subjects perform maximally. For each patient, the highest value of the inhalation, out of 3 repeat inhalations, was selected for analysis (24,25).…”
Section: Measurement Protocolmentioning
confidence: 99%
“…Among the DPIs that deliver LABA/LAMA, Breezhaler Ò has the lowest airflow resistance, followed by Ellipta Ò and Genuair Ò [61] (Table 2). Moreover, a recent study showed that patients with COPD were able to inhale with the least inspiratory effort and generate the highest mean PIF via the Breezhaler Ò inhaler than with the Ellipta Ò and HandiHaler Ò inhalers, irrespective of patients' COPD severity, age, or gender [62]. Low resistance characteristics could explain patient-reported ''comfort'' inhaling through some devices; the flow rate produced by a standard pressure drop of 4 kPa was greater using Breezhaler Ò than other DPI devices in vitro [63].…”
Section: Characteristics Of Laba/lama Inhaler Devices: Drug Depositiomentioning
confidence: 99%
“…3 For example, the ability to generate higher inspiratory flows might be limited in patients who have muscle weakness, small stature, or severe to very severe airflow limitation. [13][14][15] A minimal PIF of at least 30 L/ min is suggested for Diskus (GlaxoSmithKline), and of at least 20 L/min for HandiHaler (Boehringer Ingelheim), 8 for the patient to actuate the DPI and inhale the fine drug particles into the lungs; whereas a PIF of at least 60 L/min 8 and of at least 30 L/min 8 or 40 L/min 16 is considered optimal for Diskus and HandiHaler, respectively. Several methods, including the In-Check DIAL device and flow-volume measurements, can be used to measure PIF.…”
mentioning
confidence: 99%
“…Previous studies have reported undertaking a total of three consecutive measurements of PIF and using the highest recorded value. 9,11,13,15,18 The American Thoracic Society/ European Respiratory Society spirometry guidelines suggest at least three measurements if the repeatability criteria are met. If repeatability criteria are not met, up to eight measurements can be attempted.…”
mentioning
confidence: 99%